2013
DOI: 10.1007/s11357-013-9537-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-senescence efficacy of radio-electric asymmetric conveyer technology

Abstract: Recent evidence suggests that ageing-related diseases could result in an accelerated loss of self-renewal capability of adult stem cells, normally involved in replacing damaged cellular elements. In previous works, we highlighted that a specific treatment, named tissue optimization-regenerative (TO-RGN), of radio-electric asymmetric conveyer (REAC) technology, influenced gene expression profiles controlling stem cell differentiation and pluripotency of human skin-derived fibroblasts in vitro. The purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 30 publications
4
34
0
4
Order By: Relevance
“…Furthermore, REAC TO-RGN exposure proved effective in antagonizing the aging process in vitro 333435. Here, we show that REAC TO-RGN exposure also affected telomerase-dependent senescence mechanisms, by transcriptionally enhancing the expression of TERT, and counteracting telomere shortening.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, REAC TO-RGN exposure proved effective in antagonizing the aging process in vitro 333435. Here, we show that REAC TO-RGN exposure also affected telomerase-dependent senescence mechanisms, by transcriptionally enhancing the expression of TERT, and counteracting telomere shortening.…”
Section: Discussionmentioning
confidence: 62%
“…For these reasons, researchers in recent years have been trying to dissect the epigenetic modifications involved in cellular aging, in an attempt to reverse stem cell senescence and achieve rejuvenation [32,33]. Physical stimuli such as electromagnetic fields have been largely applied to slow down cell senescence, by modulating cell polarity and the expression of the aging related markers, such as TERT, p16INK4, ARF, p53, and p21, together with the activity of beta-galactosidase [21,[34][35][36]. Moreover, other authors demonstrated that Rapamycin can inhibit mTOR and its signalling pathway, restoring both the self-renewal and the potency of stem cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…This effect resulted from and was associated with (i) the activation of a telomerase dependent pathway, linked to the re-expression of TERT, the gene coding for the catalytic core of telomerase with subsequent increase in telomere length [77], (ii) the induction of a telomerase independent pathway associated with the activation of Bmi-1 and the transient increase in the expression of pluripotency genes, such as Nanog, Sox2 and Oct4 [77], and (iii) the resumption of multilineage differentiation potential, as shown by recovery of high throughput of differentiation along vasculogenic, osteogenic, and adipogenic fates [78].…”
Section: Cancer Stem Cells: Foe or Reprogrammable Cells For Efficientmentioning
confidence: 99%